Transformative environmental threats: behavioral and attitudinal change five years after the deepwater horizon oil spill. Issue 4 (2nd October 2017) - Bergstrand, Kelly; Mayer, Brian
ABSTRACT: Does experiencing an environmental disaster have the transformative power to change people's attitudes, behaviors and political actions? Do these effects persist in the longer term? And what elements of environmental disasters are most effective at spurring change? Using survey data collected in two affected coastal counties around the five-year anniversary of the Deepwater Horizon oil spill, we find that many residents reported mobilizing effects from the disaster: over two-thirds of respondents participated in political activities, about half engaged in environmentally friendly lifestyle changes and about half of the respondents reported more concern for the environment. We also investigate whether certain grievances are more or less powerful in their transformative consequences, and differentiate damages caused by perceived economic losses, social corrosion, physical health effects, ecological degradation and emotional reactions. Interestingly, the strongest predictor of political, behavioral or attitudinal changes was whether residents were affected emotionally by the oil spill, like feeling angry or distressed. Surprisingly, perceived economic losses had few effects, with the exception of becoming more opposed to offshore drilling. These results suggest that environmental threats can motivate political, lifestyle or attitudinal changes and that certain elements of the experience may have more mobilizing power than others.